DETERMINAN PREFERENSI MASYARAKAT MUSLIM DALAM MEMILIH HOTEL SYARIAH - Muhammad Khairur Rijal; Muhammad Yafiz; Yenni Samri J (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2020)
This research tries to analyze the factors that determine the preferences of Medan's Muslim community towards the selection of sharia hotels. The method used in this research is quantitative by taking a sample of 100 people from the Muslim City community who stay at the Sharia Hotel chosen by the researcher. The method of data analysis uses multiple linear regression with the help of SPSS Version 21.0. From the results of research conducted showed that the partial variables are also simultaneous price, halal, facilities, interests and motivation towards the preferences of the Medan City Muslim community in the selection of sharia hotels. From these variables, the overnight stay of finance from the sharia hotel sector in Medan increased.